Kesenjangan Kualitas Layanan Madrasah Aliyah Negeri di Jawa dan Luar Jawa - Fauziah Khoiriyani; Fatimatuz Zahro Diah Putri Dani; Rahmat Husein Andri Ansyah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
Madrasah service quality gap is a big challenge in Indonesia national development, especially in the comparative perspective of Java and non-Java regions. Continuous and systematic efforts have been examined to close the gap. Related to this, this study aims to look at the perceptions, comparisons, and dimensions that need to be improved in the quality of service at Madrasah Aliyah Negeri (MAN) on Java and outside Java. This research uses a mixed-method approach with a sequential explanatory method. Each of the ten MAN on Java and outside Java is used as the object of research with a total of 3,319 samples, 1803 respondents from MAN on the island of Java and 1516 outside the island of Java. The results indicate that the perceived service quality at MAN is generally good, with an average rating of 5.64 in Java and 5.27 outside Java. The rating in Java is slightly higher than outside Java, with a statistically significant difference between the two sample groups, as shown by the t-value of 4.083 exceeding  the  t-table value  of 1.990. Meanwhile,  the  dimensions  of service quality  that need to  be improved by MAN on Java Island are assurance, while outside Java are assurance and tangible.